Contemporary Ijtihād and the Reform of Islamic Family Law in Indonesia - Nayel Arsyad Rahman; Izran Danendra Pratama (The Indonesian Journal of Islamic Legal Modernism, 2026)
The development of Indonesian society has generated new legal and social challenges that require adaptive interpretations of Islamic law, particularly in the field of family law. This study examines the role of contemporary ijtihād in the reform of Islamic family law in Indonesia, focusing on how modern legal reasoning contributes to the reconciliation of Islamic principles with evolving social realities. Employing a normative and doctrinal approach within the framework of Islamic legal modernism, the research analyzes legislative developments, judicial practices, and contemporary scholarly interpretations related to marriage, divorce, child custody, and inheritance. The findings indicate that contemporary ijtihād has played a significant role in promoting legal reforms aimed at strengthening gender justice, child protection, and family welfare while maintaining conformity with fundamental Islamic values. The study further reveals that Indonesian Islamic family law reflects a dynamic interaction between classical jurisprudence, national legal institutions, and contemporary social demands. Reform efforts demonstrate the flexibility of Islamic legal reasoning in addressing issues that were not explicitly contemplated within traditional legal contexts. However, debates persist regarding the limits of legal reinterpretation and the preservation of religious authenticity. The research argues that contemporary ijtihād serves as an essential mechanism for ensuring the relevance and responsiveness of Islamic law within a modern pluralistic society. The study concludes that Islamic family law reform in Indonesia illustrates the capacity of Islamic legal modernism to balance continuity and change, thereby contributing to the development of a legal system that is both socially responsive and religiously legitimate. These findings enrich scholarly discussions on legal reform, Islamic jurisprudence, and modernization in contemporary Muslim societies.